KONSTRUK PENGEMBANGAN INDUSTRI HALAL UMKM MELALUI PENGUATAN EKONOMI DIGITAL DI INDONESIA - Handry Cahyopy (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2024)
Digital technology as a key component of the industrial revolution is one of the crucial inputs for the halal MSME industry to expand its business lines. This study aims to find out the portrait of the digital economy constructs as a means of developing the MSME halal industry in Indonesia. This type of research is qualitative research which is library research. Sources of data come from secondary data obtained through articles, journals, documentation books, and the internet, including data published by institutions that have trusted credibility, such as Bank Indonesia (BI), Ministry of National Planning and Development, and related institutions. other. Based on the search, three important strategies were found in efforts to develop the MSME halal industry through strengthening the digital economy, namely: 1) Encouraging the formation of halal MSME human resources who understand the digital economy, 2) Encouraging digital transformation for halal MSME, 3) Utilizing Industry 4.0 technology to encourage MSME growth halal which focuses on HVC by utilizing digital economic infrastructure. The three main programs (quick-wins) recommended are: 1) Developing online marketplaces and halal payment systems for MSMEs, 2) Providing digital business guidelines and sharia compliance for MSMEs that are accessible to the public, 3) Increasing digital and halal literacy value-chain for SMEs with various programs.